Effect of ceria coating on corrosion behaviour of low alloy steel. (September 2013) - Ghosh, D; Shukla, A K; Mitra, S K
Abstract : This paper investigates the effect of cerium oxide (CeO2 ) coating on the high temperature corrosion behaviour of normalised and tempered 2·25Cr–1Mo steel in oxidation–sulphidation (SO2 +O2 ) mixed gas environment. The CeO2 coating of two different coating thicknesses (150 and 300 μm) is prepared for experimental investigations. The isothermal corrosion study of uncoated and different CeO2 coated specimens is carried out in SO2 +O2 environment at 973 K. The external scales of the post-corroded specimens are characterised after corrosion test by scanning electron microscopy and X-ray diffraction. CeO2 coated specimens show higher corrosion resistance than uncoated specimen. The higher corrosion resistance of CeO2 coated specimens is associated with excellent scale plasticity and adhesion. The detailed mechanism of the corrosion is discussed in the paper.